Evaluation of Mangrove, Acanthus ilicifolius Aqueous Extract on Inhibition of Dengue Virus Replication: In Vitro and Molecular Docking Approach - Wiradana, Putu Angga; Wiartini, Ni Wayan Ayu Wiartini; Sucipto, Teguh Hari; Herdiansyah, Mochammad Aqilah; Permatasari, Anak Agung Ayu Putri; Widhiantara, I Gede; Sari, Ni Kadek Yunita Sari; Darmanto, Win; Panjaitan, Novaria Sari Dewi Panjaitan; Kusala, Muhammad Khaliim Jati Kusala (Institute of Topical Disease Universitas Airlangga, 2025)
Dengue virus (DENV) infection is a worldwide health risk, presenting severe symptoms with possibly lethal consequences. The search for effective antiviral drugs against DENV has largely focused on natural products. Mangrove, Acanthus ilicifolius, has been empirically shown to exhibit various biological activities and good safety profiles. The purpose of this investigation was to examine the antiviral activity of A. ilicifolius aqueous extract against DENV, and the way it functions of action of its bioactive components function was explored utilizing an in vitro and molecular docking method. Aqueous extract of A. ilicifolius leaves was made, and its therapeutic potential was examined using half cytotoxic concentration (CC50) and effective concentration (EC50) on Vero cells using the MTT method. The selectivity index (SI) value was determined from the ratio of CC50 and EC50. A total of 12 ligand compounds reported to be contained in the extract were prepared for molecular docking using AutoDock Vina, followed by in silico drug-like potential. A. ilicifolius water extract achieved the greatest Vero cell viability rate of 159.80% at a concentration of 31.25 μg/mL. A. ilicifolius extract at 100 μg/mL demonstrated the greatest DENV-3 inhibitory rate of 79.69%. The CC50 value was 78.55 μg/ml, and the EC50 value was 64.37 μg/mL. The SI value calculated from the ratio of CC50 to EC50 was 1.22. Molecular docking identified stigmasterol, stigmasterol-3-O-β-d-glucopyranoside, and quercetin as the primary compounds with the greatest docking values (-7.9 kcal/mol, -7.6 kcal/mol, and -7.7 kcal/mol, respectively). The findings of this study demonstrate the anti-DENV capability of the A. ilicifolius extract compound, which can limit viral multiplication via biological agents that interact with virus attachment within host cells, with an SI value of 1.22.